ADVANCED RADIOLOGY METHOD FOR MONITORING PROGRESSIVITY OF PAEDIATRIC MENINGOENCEPHALITIS: A CASE REPORT - Novia Bella Rianto (Faculty of Medicine Universitas Kristen Duta Wacana, 2021)
Introduction Meningitis is a disease characterized by infection and inflammation of the meninges, caused by microorganisms. Encephalitis is inflammation of brain. Meningoencephalitis is inflammation of the meninges and brain. The microorganisms that most often cause meningoencephalitis are viruses and bacteria. Bacterial meningitis has more severe clinical manifestations and is fatal if not treated effectively. The Global Burden of Disease study showed that meningitis caused 318,000 deaths each year worldwide. Aim The aim of this case study is to report a case of meningoenchepalitis in a 7 year old girl. Case Description A 7 year old girl presented with recurrent seizures within 24 hours and seizures for 3 hours. The patient has a history of fever, runny nose and sore throat. The results of physical examination showed nuchal rigidity, right side hemiparesis. The patient was conducted to a head MSCT examination without contrast on September 24 and 28, 2020 and cerebrospinal fluid examination to determine the microorganism. The patient was given treatment and then an MRI examination of the head was carried out on October 5, 2020. Conclusion Meningoenchepalitis is a disease characterized by infection and inflammation of the meninges and brain. Symptoms associated with meningitis include fever, headache, stiff neck. One of the supporting tests that can be done is head MSCT. Neuroimaging meningitis examination in children can identify predisposing factors and complications that occur. Keywords: meningitis, children, computed tomography, magnetic resonance image